2018
DOI: 10.1116/1.5016241
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of ion fluxes incident at the substrate plane during reactive high-power impulse magnetron sputtering of groups IVb and VIb transition metals in Ar/N2

Abstract: Reactive transition-metal (TM) nitride film growth employing bias-synchronized high power impulse magnetron sputtering (HiPIMS) requires a detailed knowledge of the time evolution of metal-and gas-ion fluxes incident at the substrate plane in order to precisely tune momentum transfer and, hence, provide the recoil density and energy necessary to eliminate film porosity at low deposition temperatures without introducing significant film stress. Here, we use energy-and time-dependent mass spectrometry to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…A pulsed substrate bias V s = -500 V is applied synchronously with 110-μs-HiPIMS pulses, based upon time-and energy-resolved mass spectroscopy analyses performed at the substrate position, which revealed the time-and energy-integrated W + /(Ar + + N 2 + ) ion ratio during W-HiPIMS pulse as high as ~100. 15 The bias offset is set at 20 μs, which corresponds to the transit time for most energetic W + ions at the shortest target-substrate separation. The bias pulse length is set at the maximum available value of 200 μs to ensure energetic W + bombardment even at the longest target-substrate distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulsed substrate bias V s = -500 V is applied synchronously with 110-μs-HiPIMS pulses, based upon time-and energy-resolved mass spectroscopy analyses performed at the substrate position, which revealed the time-and energy-integrated W + /(Ar + + N 2 + ) ion ratio during W-HiPIMS pulse as high as ~100. 15 The bias offset is set at 20 μs, which corresponds to the transit time for most energetic W + ions at the shortest target-substrate separation. The bias pulse length is set at the maximum available value of 200 μs to ensure energetic W + bombardment even at the longest target-substrate distance.…”
Section: Methodsmentioning
confidence: 99%
“…W + irradiation is selected based on previous ion mass spectrometry studies performed at the substrate position, which showed severe Ar rarefaction during HiPIMS pulses, while sputtering in Ar/N 2 gas mixtures to such extent that the time-and energy-integrated metal/gas ion ratio during W-HiPIMS pulse was ~100. [14][15] Such conditions imply large flexibility in the choice of bias pulse offset and pulse length as both Ar + and N 2 + ion fluxes are essentially eliminated during the time period of several hundred μs following the ignition of the HiPIMS pulse. This allows efficient W + irradiation of the growing film surface, while minimizing Ar + incorporation, even when the substrate-target separation is continuously changing during substrate rotation, by using relatively long bias pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Hecimovic et al [63] investigated in detail the origin of the IEDF in HiPIMS and found that the high energy tail can be fitted with a Maxwell distribution, which indicates that the sputtered ions are also thermalized, though this will depend a lot on the pressure and the distance between the target and the substrate [62]. It is also common to see a distinct energy shoulder between the thermal ion population and the high energy tail [64,67,102,[104][105][106][107] and this was argued by Maszl et al [103] to be due to the presence of self-organizing ionization zones called spokes [108][109][110][111], which results to a potential hump that can accelerate ions [103,112]. An example of the IEDF of Ti + ions in a HiPIMS discharge is shown in Fig.…”
Section: Iedf In Hipimsmentioning
confidence: 99%
“…An additional feature of HiPIMS discharges is a time separation between metal-and gas-ion fluxes incident at the substrate due to the rarefaction of working gas in front of the target [84,88]. This effect can be utilized during the film growth to independently control the momentum and energy of incident ionized species through the application of substrate bias pulses (metal-ion-synchronized HiPIMS) [88][89][90]. This approach has been employed in papers II and III of this thesis.…”
Section: High Power Impulse Magnetron Sputteringmentioning
confidence: 99%